Pylorus resection versus pylorus preservation in pancreatoduodenectomy (PyloResPres): study protocol and statistical analysis plan for a German multicentre, single-blind, surgical, registry-based randomised controlled trial - Ulrich Mansmann; Jens Werner; Bernhard W Renz; Christine Adrion; Carsten Klinger; Matthias Ilmer; Jan G D’Haese; Heinz-J Buhr (BMJ Open, 2021)
Introduction Partial pancreatoduodenectomy (PD) is the treatment of choice for various benign and malignant tumours of the pancreatic head or the periampullary region. For reconstruction of the gastrointestinal passage, two stomach-preserving PD variants exist: pylorus preservation PD (ppPD) or pylorus resection PD (prPD) with preservation of the stomach. In pancreatic surgery, delayed gastric emptying (DGE) remains a serious complication after PD with an incidence varying between 4.5% and 45%, potentially delaying hospital discharge or further treatment, for example, adjuvant chemotherapy. Evidence is lacking to assess, which variant of PD entails fewer postoperative DGE.Methods and analysis The protocol of a large-scale, multicentre, pragmatic, two-arm parallel-group, registry-based randomised controlled trial (rRCT) using a two-stage group-sequential design is presented. This patient-blind rRCT aims to demonstrate the superiority of prPD over ppPD with respect to the overall incidence of DGE within 30 days after index surgery in a German real-world setting. A total of 984 adults undergoing elective PD for any indication will be randomised in a 1:1 ratio. Patients will be recruited at about 30 hospitals being members of the StuDoQ|Pancreas registry established by the German Society of General and Visceral Surgery. The postoperative follow-up for each patient will be 30 days. The primary analysis will follow an intention-to-treat approach and applies a binary logistic random intercepts model. Secondary perioperative outcomes include overall severe morbidity (Clavien-Dindo classification), blood loss, 30-day all-cause mortality, postoperative hospital stay and operation time. Complication rates and adverse events will be closely monitored.Ethics and dissemination This protocol was approved by the leading ethics committee of the Medical Faculty of the Ludwig-Maximilians-Universität, Munich (reference number 19-221). The results will be published in a peer-reviewed journal and presented at international conferences. Study findings will also be disseminated via the website (http://www.dgav.de/studoq/pylorespres/).Trial registration number DRKS-ID: DRKS00018842.